Effect of Trellis Conversion on the Performance of Chenin blanc/ 99 Richter Grapevines - Volschenk, C.G.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2017)
To accommodate the excessive vegetative growth of a 9-year old, 3.0 m x 1.2 m spaced and vertically trellised Chenin bland99 Richter vineyard, vines were converted to double the original cordon length by removing alternate vines or by extending the cordon laterally in a horizontal plane as per Lyre trellising system. By extending the cordon, shoot vigour was reduced, resulting in an improvement in canopy appearance and microclimate, particularly in the case of the latter system (higher canopy:root volume ratio). Yield increased by 11 % and 65% for the vertically trellised vines with extended cordon length and those on the Lyre system, respectively.  Grape composition was not affected, whereas the severity of Botrytis infection tended to decrease. Wine typicity was enhanced by trellis conversion. Labour input in terms of pruning, harvesting and seasonal canopy management was lower for the vertically trellised vines with extended cordon length, but higher for the vines on the Lyre system; the additional yield, however, still resulted in respectively 15 % and 69 % higher total income. The results showed that the "original" vigour (growth capacity) was better accommodated and distributed by extending cordon length, particularly for the Lyre system, thereby resulting in higher yields of at least similar grape and wine quality and higher income than before conversion.